Pengaruh Quality of service dan Strategi Promotion Terhadap Kepuasan Pelanggan UMKM Kuliner di Badung - Asti Sedu Tegi; Ni Made Yudhaningsih; I Kadek Donny Wishanesta (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to analyze and test the influence between the variables studied in this research. The influences tested include the partial and simultaneous influence of quality service and promotion on customer satisfaction. The type of research used in this research is a quantitative approach. The number of samples in this research was 130 Waroeng Pan Yoga customers. The data collection method in this research used observation and questionnaires. The measurement scale used in this research is the Likert scale. The data analysis techniques in this research are descriptive analysis, classical assumption test, multiple linear regression analysis and hypothesis testing consisting of the f test, t test and determinant coefficient. The data in this study was processed using SPSS 21 for Windows. The results of this research show that partially the quality service and promotion variables have a positive and significant effect on customer satisfaction, which is shown by values ​​of 0.005 and 0.006, which means <0.05. Simultaneously, the quality service and promotion variables have a positive and significant influence on customer satisfaction, 0.000, which means <0.05. The suggestion in this research is for companies to pay attention to quality service and promotion factors to increase customer satisfaction.